2021
DOI: 10.1177/10760296211034579
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of a Derived Neutrophil-Lymphocyte Ratio in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: The systemic immune-inflammatory index (SII) and derived neutrophil-lymphocyte ratio (dNLR) are novel indexes that simultaneously reflect the host inflammatory and immune status and have prognostic value in some cancers. SII was associated with major cardiovascular events in coronary artery disease patients who received percutaneous coronary intervention (PCI). However, dNLR correlations with clinical outcomes in acute coronary syndrome (ACS) patients undergoing PCI remain unclear. This study aimed to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Monocyte may be more closely related to the development of atherosclerosis than platelet. SII was shown to be positively correlated with SYNTAX score ( 35 , 36 ), which could be used for CAD risk stratification and prognostic prediction after PCI. Jin and colleagues found that the high rates of stroke and all-cause death corresponded to high levels of SII and SIRI, while the high risk of MI was only independently related to high SIRI ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte may be more closely related to the development of atherosclerosis than platelet. SII was shown to be positively correlated with SYNTAX score ( 35 , 36 ), which could be used for CAD risk stratification and prognostic prediction after PCI. Jin and colleagues found that the high rates of stroke and all-cause death corresponded to high levels of SII and SIRI, while the high risk of MI was only independently related to high SIRI ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NLR has been studied as a marker of severity and prognostication due to its ability to identify states of extreme physiological stress. Its use has been extensive in different diseases and conditions, including rheumatic diseases 13 , 22 , acute pulmonary embolism 21 , 26 , acute coronary syndrome 14 , 20 and acute pancreatitis 27 . The use of NLR in predicting the severity of community-acquired pneumonia (CAP) has been intensively studied 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we described the SII, dNLR, NLR, PLR, and MLR as suitable laboratory markers for identifying high-risk ACS patients after PCI. 10 , 11 In recent years, new systemic inflammation markers, such as AISI, SIRI, and NLPR, have attracted the attention of many researchers because they include multiple components of CBC and are also easy to obtain. Monocytes and neutrophils are part of the innate immune system and produce pro-inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Recently published studies have demonstrated that many combined ratios of CBC parameters, such as systemic immune-inflammatory index (SII), derived neutrophil-to-lymphocyte ratio (dNLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR), could be useful prognostic markers in ACS patients undergoing PCI. 10 , 11 Furthermore, as more complicated and newly mentioned inflammatory markers, the aggregate index of systemic inflammation (AISI), systemic inflammation response index (SIRI), and neutrophil-to-lymphocyte*platelet ratio (NLRP) have only been proposed simultaneously as biomarkers for predicting mortality in COVID-19 patients. 9 , 12 , 13 However, no studies have investigated the prognostic capacity of these 3 novel indices for ACS prognosis.…”
Section: Introductionmentioning
confidence: 99%